(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
In this study, the researcher aimed to define and measure the relevance and effect of the governmental organizations in complying with Iraqi Ministry of Transportation’s requirements towards achieving the social responsibility, embodied in the ten commandments of the United Nations Findings displayed the availability of realization regarding organization managers towards social responsibility with their various capabilities and tendencies in relation with the representing entries of those Ten Commandments.The study showed the relation between the effectiveness of those organizations and dimensions of the ten commandments of social responsibility, with the existence of a significant effect for the said effectiveness on achieving those Ten Commandments.The study recommended the necessity of paying more interest to the social responsibility of those organizations, and setting up an obvious strategy to achieve this.